PENDAMPINGAN BELAJAR SISWA UNTUK MENINGKATKAN KEMAMPUAN MENGGAMBAR DENGAN MODEL PEMBELAJARAN PROJECT-BASED LEARNING - Imam Mashuri; Ahmad Aziz Fanani; Riris Wahyuningsih; Salmahtus Sholekhah (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2021)
Drawing is a form of soul expression that is poured into a flat field of paper, blackboard, picture books and so on. This learning assistance program is carried out directly at home and online during the Covid-19 period. The subject of the program was a student at SD Negeri 6 Setail. This program aims to improve the drawing ability of elementary school students. The result of learning assistance is before (students are lazy to learn, monotonous learning, ability and creativity of drawing students is inhibited) and after (students are enthusiastic and more diligent in learning, learning using media that is interesting and fun, the ability and creativity of drawing students develop)